Workstation configuration and container type influence upper limb posture in grocery bagging. (November 2018) - Lang, Angelica E.; Maciukiewicz, Jacquelyn M.; Vidt, Meghan E.; Grenier, Sylvain G.; Dickerson, Clark R.
Abstract: Introduction: Repetitive movements and awkward postures are two persistent injury risk factors for grocery store cashiers. Due to the recent rise in popularity of environmentally-friendly grocery bagging options, current recommendations for cashiers are likely outdated. Correspondingly, the objective of this study was to examine the effects of cashier-specific work demands, workstation configuration, and container type on upper limb postures during typical job activities. Methods: Fifteen experienced cashiers bagged groceries at varying combinations of workstation height (low, medium, high) and container type (reusable bins, reusable bags, plastic bags). Upper limb movement was quantified with motion capture and amplitude probability distribution functions of humeral elevation and humeral axial internal rotation were used to assess the static (10th percentile), median (50 th percentile), and peak (90 th percentile) postural demands, which were then interpreted in the context of existing postural guidelines. Results: High workstation height and reusable bags increased right arm elevation at peak posture by 15.7° compared to the low workstation height and reusable bin combination. However, reusable bins increased internal rotation demands of the right arm by 4.3° compared to other container types. Left arm elevation and internal rotation were consistently lower than right arm angles. Conclusion: Cashiers are encouraged to adjust the workstation to decrease the arm elevation and internal rotation required by higher workstation heights and tall containers, and to use both arms for scanning and packing, when possible, to reduce undesirable arm postures. Highlights: Reusable containers (bags and bins) generally increased arm elevation levels. Both reusable and plastic bags increased arm internal rotation. Highest arm elevations at high workstation height with reusable containers. Right side (closest to conveyor) experienced higher postural demands.